Legal Framework For Termination Of Contract Due To Force Majority To Further Ensure Legal Certainty - Manurung, Doni Freddi; Siregar, Mahmul; Robert (Universitas Sumatera Utara, 2025)
Contracts essentially arise from differences in interests between parties bound in a legal relationship. In practice, not all contracts can be executed as initially agreed, especially due to force majeure conditions. However, the Indonesian Civil Code does not explicitly detail the events that constitute force majeure, leading to legal uncertainty. This study aims to examine the legal framework for contract termination due to force majeure in order to ensure legal certainty for the parties. The research is normative legal research using statutory and case approaches, utilizing both primary and secondary data obtained through literature and document study. The findings indicate that Articles 1244 and 1245 of the Civil Code serve as the primary legal basis for force majeure, stating that a party unable to fulfill obligations due to such circumstances may be exempt from liability. However, practical implementation depends heavily on contract clauses and the burden of proof. Courts consider several aspects such as the force majeure clause, duration, good faith, and mitigation efforts in their rulings. The study concludes that although a legal framework exists, more detailed and flexible regulations are needed to address the complexities of modern contractual relationships and ensure greater legal certainty. Therefore, it is recommended that the government develop additional legal instruments regulating force majeure in contractual agreements in Indonesia.